Manajemen Pengolahan Koleksi Buku di Dinas Kearsipan dan Perpustakaan Kota Jambi - Jamaluddin Jamaluddin; Sumirah Sumirah; Hariyati (JMiE (Journal of Management in Education), 2022)
This study aims to determine the management of book collections, as well as the challenges and efforts made by the Jambi City Library and Archives Office. This research uses qualitative techniques and descriptive research design. Interviews, observations, and documents are used as data collection strategies. Data reduction, visualization, and verification techniques are used in data analysis (conclusions). Based on the results of field research, the management of book collections at the Jambi City Archives and Library Office includes the procurement of books, data verification, intervention, book stamps, classification, cataloguing, making cards and book bags, as well as providing barcodes before being placed on the bookshelf. In accordance with applicable norms and regulations, the number of books in the Jambi City Archives and Library Office is sufficient. Evaluate human resources by offering advice and training, and presenting them to librarian managers.